The influence of ethnicity on the symptoms of post-reproductive women - Belešová, Romana; Tóthová, Valérie (Journal of Nursing, Social Studies and Public Health, 2022)
Theoretical basis: The menopause is a period in women’s lives when their ability to reproduce decreases, and as it gradually ends, women move into the so-called post-production phase. In this transitional phase, women are at risk of developing various symptoms, which are affected by more factors than only a deficiency of ovarian hormones (estrogens). Many recent international studies have shown the influence of other factors on women‘s health during this period, such as the family environment, interpersonal relationships, employment, and ethnic and cultural aspects. Goal: The literature review is devoted to the research of published studies dealing with the influence of ethnicity and culture on the occurrence of symptoms and health of women in the post-reproductive phase of their lives. Methods: We searched for the included studies using the method of content analysis. The scientific databases focused on women’s health, and studies published between 2017 and 2022 were found in databases such as PubMed, Scopus, ScienceDirect, and EBSCO. We used the keywords “ethnicity”, “menopause”, “symptom”, “influence”, “woman”, and the Boolean operator “AND”. The content analysis took place from January to February 2022. After checking the eligibility and relevance of studies, we included and analysed eight articles. Results: It is clear from the literature review results that ethnic and cultural factors are involved in vasomotor, somatic, and cognitive symptoms in women with estrogen deficiency. Conclusions: The information obtained can be helpful, and used in providing individual holistic care to women of different ethnicities in both primary care and inpatient health facilities.